Development of Sustainable PPE for Higher Threat Clearance Operations by Humanitarian Organisations - Brown, Laura (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: PPE; Natural Fibres; Ballistics; Armour; DSDS23; DSDS23 Poster